Neglected intrapulmonary arteriovenous anastomoses: A comparative study of pulmonary right-to-left shunts in patients with patent foramen ovale - Chen, Anni; Zhu, Jianbo; Zhu, Lei; Tang, Yunyi; Li, Yun; Zhang, Qi; Zhao, Yeping; Ma, Caiye; Liu, Xiatian (Frontiers in Cardiovascular Medicine, 2023)
Objective: Pulmonary right-to-left shunt (P-RLS) and patent foramen ovale right-to-left shunt (PFO-RLS) often appear in combination, and there are often differences and connections between them. This study aimed to further clarify the incidence and characteristics of P-RLS with the help of transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) combined with saline contrast echocardiography, providing a reference for clinically relevant research and patent foramen ovale (PFO) management disposal decisions. Methods: We studied patients aged 18-65 years who came to our hospital for TTE from October 2021 to July 2022 with a high clinical suspicion of PFO. All patients were screened by TTE, and according to the examination results, the positive patients were then diagnosed by TEE. In the process, we observed the presence of P-RLS, then identified and investigated it in association. Results: A total of 157 patients with PFO diagnosed by TEE were included in the final analysis. Whether at rest or after Valsalva maneuver, the incidence of P-RLS was significantly higher under contrast transesophageal echocardiography (c-TEE) than under contrast transthoracic echocardiography (c-TTE) (at rest: 73.9% vs. 45.2%, P<0.001; after Valsalva maneuver: 82.2% vs. 52.2%, P<0.001). For both c-TTE and c-TEE, the incidence of P-RLS was slightly higher after Valsalva maneuver than at rest, but the difference was not significant (c-TTE: P = 0.214; c-TEE: P = 0.076). In the same state, the number of patients with high P-RLS semiquantitative grading under c-TEE was greater than that under c-TTE, and the semiquantitative grades of P-RLS were significantly different between c-TTE and c-TEE (all P < 0.001). Under the same examination mode, the number of patients with high P-RLS semiquantitative grading after Valsalva maneuver was greater than that at rest, and there were significant differences in the P-RLS semiquantitative grades between the Valsalva maneuver and the resting state (all P < 0.001). Conclusion: The vast majority of P-RLS are grade 1-2 and are derived from physiological IPAVAs. Even so, attention should be given to the differentiation between P-RLS and PFO-RLS. c-TEE is an effective method to detect P-RLS, however, the recruitments of TEE and VM to P-RLS should be noted.